Solve the system by substitution. \[ \begin{aligned} y & =3 x+28 \\ y & =-4 x\end{aligned} \]
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To solve the system by substitution, we start with the two equations provided: 1. \( y = 3x + 28 \) 2. \( y = -4x \) Since both equations equal \( y \), we can set them equal to each other: \[ 3x + 28 = -4x \] Now, we'll solve for \( x \) by adding \( 4x \) to both sides: \[ 3x + 4x + 28 = 0 \] \[ 7x + 28 = 0 \] Next, subtract 28 from both sides: \[ 7x = -28 \] Now, divide both sides by 7 to find \( x \): \[ x = -4 \] Now that we have the value for \( x \), we can substitute it back into either original equation to find \( y \). We'll use the second equation for simplicity: \[ y = -4(-4) = 16 \] Thus, the solution to the system of equations is: \[ (x, y) = (-4, 16) \]